2007
DOI: 10.1111/j.1440-1681.2007.04736.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Increases Contralateral Testicular Ischaemia–reperfusion Injury After Unilateral Testicular Torsion

Abstract: 1. Testicular ischaemia-reperfusion injury is commonly seen in childhood. Infertility occurs in 25% of patients after unilateral testicular ischaemia. It is has been reported that methylene blue has a positive effect in the reparation of ischaemia-reperfusion injury in different tissues. Therefore, we hypothesized that methylene blue may prevent the hazardous effects of ischaemia-reperfusion injury in testicular tissue after unilateral testicular torsion. 2. Thirty-two prepubertal Wistar-albino rats were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The results obtained in the present study are similar to those reported by some researchers [28][29][30] but differ from those reported by Rezzani et al 31 and Aksu et al 32 . The differences may be due to the difference in organ systems used, the dose and mode of application of the MB used in these studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results obtained in the present study are similar to those reported by some researchers [28][29][30] but differ from those reported by Rezzani et al 31 and Aksu et al 32 . The differences may be due to the difference in organ systems used, the dose and mode of application of the MB used in these studies.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, it is reported that MB exposure for 5 hours on either ipsilateral or contralateral testes did not ameliorated biochemical or histological parameters in unilateral spermatic cord torsion model 30 . On the contrary, systemic administration of MB has been shown to reduce oxidative stress in kidney of ciclosporine treated rats 31 .…”
Section: Discussionmentioning
confidence: 92%